2020
DOI: 10.1093/mnras/staa2702
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the distance to the North Polar Spur with Gaia DR2

Abstract: The North Polar Spur (NPS) is one of the largest structures observed in the Milky Way in both the radio and soft x-rays. While several predictions have been made regarding the origin of the NPS, modelling the structure is difficult without precise distance constraints. In this paper, we determine accurate distances to the southern terminus of the NPS and toward latitudes ranging up to 55○. First, we fit for the distance and extinction to stars toward the NPS using optical and near-infrared photometry and Gaia … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(55 citation statements)
references
References 44 publications
2
48
0
Order By: Relevance
“…This is a strong indication that at high latitude Loop I, which dominates the polarized synchrotron emission in the area, is located within this range of distances. This conclusion is in agreement with several other determinations of the distance to Loop I (e.g., Salter 1983;Vidal et al 2015;Planck Collaboration et al 2016b;Das et al 2020).…”
Section: Loop Isupporting
confidence: 93%
See 2 more Smart Citations
“…This is a strong indication that at high latitude Loop I, which dominates the polarized synchrotron emission in the area, is located within this range of distances. This conclusion is in agreement with several other determinations of the distance to Loop I (e.g., Salter 1983;Vidal et al 2015;Planck Collaboration et al 2016b;Das et al 2020).…”
Section: Loop Isupporting
confidence: 93%
“…Soon after its discovery, Bingham (1967) found that the electric vector position angles (polarization angles) of a small number (≈10) of stars were aligned with the B-field direction traced by synchrotron polarization, thus suggesting a distance of ∼100 pc to the high-latitude part of Loop I. Subsequent studies of the optical polarization have confirmed this conclusion (Spoelstra 1972;Ellis & Axon 1978;Leroy 1999;Santos et al 2011;Berdyugin et al 2014) and are in agreement with the distance to the neutral gas likely associated with the NPS (Puspitarini & Lallement 2012;Das et al 2020). In apparent contradiction with these determinations, an alternative model has been proposed for Loop I, in which the structure is located at the Galactic center and forms part of a bipolar hyperbubble extending out to the Galactic halo (Sofue 1977(Sofue , 2000.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…The top panel of Fig. 12 shows the presence of high-latitude dust within the 500 pc sphere around the Sun, confirming that the so-called North Polar Spur (the dust filament reaching up to b ∼ 45 deg at l ∼ 0 deg) is a local structure and not related to the Fermi bubbles produced by the Galactic centre (see Das et al 2020 for a comprehensive discussion).…”
Section: Extinction Mapsmentioning
confidence: 58%
“…Rows two to five: ASS, LSA, BSS, and QSS models for the GMF, respectively. well localized in the sky towards regions of nearby known structures (spurs, arms, and clouds) mainly attributable to the nearby structures such as the Sco-Cen association (e.g., Das et al 2020). We used the gpempy software to investigate this further and we reached the conclusion that, in general, p lin is not boosted by the simple addition of a clump of dust towards such a maximum to solve the problem.…”
Section: Alternative Comparison Of Polarization Mapsmentioning
confidence: 99%